1998
DOI: 10.1161/01.res.83.5.481
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Involvement in Translational Regulation of Fibronectin Expression by Light Chain 3 of Microtubule-Associated Protein 1 in Vascular Smooth Muscle Cells

Abstract: Abstract-Our previous studies suggested that enhanced fibronectin mRNA translation in ductus arteriosus compared with aortic smooth muscle cells is related to increased expression of light chain 3 (LC3) of microtubule-associated protein 1, which binds an AU-rich element in the 3Ј untranslated region of fibronectin mRNA. We therefore hypothesized that microtubules are involved in LC3-mediated fibronectin mRNA translational regulation. In this study we show that disruption of microtubules by colchicine inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…8). Moreover, immunoprecipitation with antiphosphotyrosine antibody followed by Western blotting with the antibody recognizing 15-kDa LC3 microtubule-associated protein 1, showed significant up-regulation of this protein (data not shown), which is also known as a factor facilitating translation of fibronectin mRNA (54). DISCUSSION Results presented in this report showed that, similar to other cell types (15)(16)(17)(18)(19), cultured SMC isolated from porcine coronary FIG.…”
Section: Resultsmentioning
confidence: 58%
“…8). Moreover, immunoprecipitation with antiphosphotyrosine antibody followed by Western blotting with the antibody recognizing 15-kDa LC3 microtubule-associated protein 1, showed significant up-regulation of this protein (data not shown), which is also known as a factor facilitating translation of fibronectin mRNA (54). DISCUSSION Results presented in this report showed that, similar to other cell types (15)(16)(17)(18)(19), cultured SMC isolated from porcine coronary FIG.…”
Section: Resultsmentioning
confidence: 58%
“…This brings forth the interesting possibility that microtubules and/or associated factors coordinate efficient translation of a subset of proteins. Supporting this idea, it has been previously reported that microtubule disruption reduces fibronectin mRNA prevalence in polyribosomes of smooth muscle cells 39 . Given these observations, it is tempting to speculate that microtubules coordinate the organization of polyribosome structures, which may be preferentially associated with a subset of mRNAs.…”
Section: Discussionmentioning
confidence: 70%
“…LC3B acts as a positive regulator of fibronectin (Fn1) mRNA translation, through direct binding to an AU-rich region of the Fn1 39-UTR (44,45). LC3B-dependent fibronectin expression and downstream increases in connective tissue growth factor expression were associated with tumor cell proliferation, adhesion, and invasiveness in fibrosarcoma cells (46).…”
Section: Discussionmentioning
confidence: 99%